Urban agriculture in the Gauteng City-Region’s green infrastructure network - Camargo Nino, Eliana; Lane, Sam; Okano, Kanako; Rahman, Irvanu; Peng, Bo; Benn, Hannah; Culwick Fatti, Christina; Maree, Gillian; Khanyile, Samkelisiwe; Washbourne, Dr Carla (Gauteng City-Region Observatory, 2020)
As cities in developing countries contend with the challenges of urbanisation, they need to rethink the traditional modes of urban planning and development. Part of this logic is to cater for growing populations without compromising urban environments and social development. Green infrastructure is one such approach that aims to meet infrastructure and service needs while ensuring the proper functioning of natural ecological systems. Urban agriculture can create multifunctional green assets in the form of urban farms and food gardens. When planned accordingly, urban agriculture can contribute to addressing a range of issues in the Gauteng City-Region (GCR). In the City of Johannesburg, the expansion of urban agriculture, and green infrastructure more broadly, aligns with and could contribute to multiple development goals. This paper interrogates whether a green infrastructure approach could offer the potential to improve urban agriculture efforts if the approach can be mainstreamed into municipal development processes. Realising the benefits of urban agriculture hinges on integrating these approaches into municipal planning and projects, as well as on improving the productivity of ecosystem service delivery from both green infrastructure and urban agriculture. The focus of this report is pertinent in light of persistent infrastructure and service delivery backlogs in the GCR, considerable challenges around food systems and food security, and a highly unequal urban spatial form – all of which impact the distribution of infrastructure and services, both green and conventional. This report argues that a green infrastructure approach is valuable for drawing important connections between focus areas related to urban agriculture that are traditionally siloed. The analysis focuses on urban agriculture in the GCR’s green infrastructure network using urban food gardens in the City of Johannesburg as the unit and site of analysis. This occasional paper falls under the Gauteng City-Region Observatory (GCRO) Green Assets and Infrastructure research and links urban agriculture and green infrastructure in the GCR together for two main reasons. First, the paper outlines how food gardens are a key component of the interconnected set of the natural and constructed infrastructure systems within the city. This framing helps to link urban agriculture and food systems research to broader municipal development goals in terms of infrastructure and service delivery. Second, the paper outlines evidence of the wider social impact of food gardens which validates the ability of green infrastructure to meet social, economic and public health goals (e.g. social cohesion, employment, economic resilience) beyond a purely environmental focus. Understanding food gardens as multifunctional green assets is one way to promote and secure investment in urban agriculture in the GCR.
Keywords: Urban agriculture, green infrastructure, Gauteng